The economics and adoption of the combine harvester in the Muda region of Malaysia. - Ayob, Ahmad Mahdzan (1979)
The objectives of this paper was to provide basic information on the diffusion of the new mechanical harvesting technology in the Muda area of Malaysia. Primary data, obtained by means of personal interviews of farmers, machine owners and machine commission agents, were used. Cross-tabulation as well as multivariate techniques were employed to describe the pattern of combine harvester adoption in the Muda region. The analysis showed that large farms were more likely to adopt the machine compared with the small farms. In the adoption process, those farmers who perceived the economic as well as technical superiority of the combine were not only more likely to adopt but adopted the machine earlier than those that did not perceive the machine's advantages. Access of the new technology to an area increases the probability of a farmer using it. To be economical, the area harvested by a combine must be large and contiguous. Farms in Muda are typically small with an average of 1.6 ha. Hence it is necessary for neighboring farms to agree to harvest their crops together before a combine can be called upon to do the job. The viability of the combine harvester as a private business project has been confirmed by another research worker. There is no doubt that the greater benefits of the new harvesting technology have accrued to the machine-owning class in the form of business profits. Another direct beneficiary of the technical change is the group that act as 'brokers' or commission agents. In so far as they are already big farmers, the introduction of the combine harvester furthers the interest of the large farms. Farmer benefits from this new technology from the reduction of harvesting cost and timely operation which could well save a crop from torrential rain. An indirect benefit to farmers stems from the addtional income obtained from part-time work on other farms not using the machine. Complete mechanization of harvesting is not envisaged in the Muda area under the present state of the arts. Large areas of the region are still inaccessible to the machine and even in areas that are accessible, uneven ripening due to uneven planting dates prevent simultaneous harvesting of neighboring plots. A lodged crop is also rejected by the machine. For these farms, the manual harvesting will continue to be important.